Spontaneous tumor regression and immunotherapy response demonstrate clonal T-cell expansion in Merkel cell carcinoma - Patrick Hallaert; John W. Roman; Mairead Baker; Natasha T. Hill; Jennifer L. Marte; James L. Gulley; Nicholas Logemann; Courtney W. Hudgens; Alexandre Reuben; Isaac Brownell (npj Precision Oncology)
Abstract Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine skin cancer that is responsive to immune checkpoint inhibitors (ICI). On rare occasion, MCC spontaneously regresses. It is speculated that this regression occurs when biopsy-induced antigen shedding precipitates an immune response. Here, we demonstrate the activation of an adaptive immune response in a patient whose tumor underwent spontaneous regression after biopsy. To evaluate the tumor immune microenvironment during regression, we performed quantitative immunohistochemical analysis and T-cell receptor (TCR) sequencing. Relative to baseline, the regressing tumor showed evidence of an activated cytotoxic T-cell response together with increased TCR clonality, greater representation of dominant T-cell clones, and the emergence of novel high-frequency T-cell clones. Similar changes in TCR profiles were observed in an MCC tumor undergoing ICI-induced regression. Taken together, our results provide evidence that the expansion of novel and pre-existing adaptive immune responses drives spontaneous MCC regression.